2018
DOI: 10.3748/wjg.v24.i7.810
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation for delayed circulating tumor cell isolation is a valid strategy for prognostic association of circulating tumor cells in gastroesophageal cancer

Abstract: AIMTo demonstrate the feasibility of cryopreservation of peripheral blood mononuclear cells (PBMCs) for prognostic circulating tumor cell (CTC) detection in gastroesophageal cancer.METHODSUsing 7.5 mL blood samples collected in EDTA tubes from patients with gastroesopheagal adenocarcinoma, CTCs were isolated by epithelial cell adhesion molecule based immunomagnetic capture using the IsoFlux platform. Paired specimens taken during the same blood draw (n = 15) were used to compare number of CTCs isolated from fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Brungs et al assessed 43 patients from whom CTCs were isolated using the standard EpCAM isolation methods at any clinical stage of GOC. In 93% of patients, where EpCAM selected CTCs were identified, a proportion also co-expressed surface uPAR (CK+/Ep-CAM+/DAPI+/CD45-/uPAR+ CTCs) [130]. In further analyses, we found that where more than 60% of these EpCAM selected uPAR+ CTCs also co-expressed uPAR, histological tumour uPAR IHC scoring was also increased (Figure 3).…”
Section: Evidence Of Upas On Circulating Tumour Cellsmentioning
confidence: 76%
“…Brungs et al assessed 43 patients from whom CTCs were isolated using the standard EpCAM isolation methods at any clinical stage of GOC. In 93% of patients, where EpCAM selected CTCs were identified, a proportion also co-expressed surface uPAR (CK+/Ep-CAM+/DAPI+/CD45-/uPAR+ CTCs) [130]. In further analyses, we found that where more than 60% of these EpCAM selected uPAR+ CTCs also co-expressed uPAR, histological tumour uPAR IHC scoring was also increased (Figure 3).…”
Section: Evidence Of Upas On Circulating Tumour Cellsmentioning
confidence: 76%
“…Eleven studies were enrolled for OS analysis, with a total of 854 EC patients [ 13 , 25 , 26 , 27 , 29 , 32 , 54 , 75 , 82 , 83 , 84 , 85 ]. In this cohort, the average age was 63.6 years (61.5–66) and the median CTC positivity rate was 46.4% (18.0–79.7).…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis is also supported by the clinical picture. CTC numbers are known to increase with disease burden 40 , and at the time of blood draw patient 20 had high volume and rapidly progressive disease. It is reasonable to suggest this patient www.nature.com/scientificreports www.nature.com/scientificreports/ had a high number of biologically relevant CTCs which were missed using standard CTC isolation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…A separate matched 7.5 ml EDTA blood sample was collected at the same blood draw for EpCAM based capture for CTC enumeration using the IsoFlux system (Fluxion Biosciences), and processed as per manufacturer instructions 43 . Enumerated CTCs were defined by the standard EpCAM/ Cytokeratin/DAPI positive and CD45 negative phenotype 40 .…”
Section: Patient Selection and Blood Collectionmentioning
confidence: 99%